If it's not what You are looking for type in the equation solver your own equation and let us solve it.
k in (-oo:+oo)
(k-75)/5 = 0
k-75 = 0 // + 75
k = 75
k = 75
| 4xb=1 | | (5x^2+4)*(6x-2)= | | x(8x+1)=3x^2-3x+1 | | 4/5x-15/4x=5/2 | | (y-6)-(y+8)=9y | | 5(x-6)=65 | | (6y-7)-(3y-5)*6=40 | | 10+0.10b=0+0.35b | | -6x-8=-7x+2 | | 8-9x-2=75+7x-15 | | -.4x+.5x+3=2 | | (y-6)-(y-8)=9y | | (2-x)(x+5)=0 | | .4x+.5x+3=2 | | 2x-40+x+x+60=900 | | 3x+12=9x-5(x+1) | | 11x+6y=-18 | | (2x+24)+y=180 | | 1.7=.25x+.1(x+3) | | 10-9x=52 | | x^5+8x^2-9x-72=0 | | x-9=16x+(-15) | | 3x^2y^-2/6Y^3 | | (1/x^2)=0 | | 5+(2E)=(3E)-2 | | 5x+12=x-12 | | 18-2/3x6 | | 10.50=.45(m-5)+2.50 | | 2x-3=70 | | 5x-2y+z=11 | | (tan^2x+1)(cos^2x-1)=-tan^2x | | 2(3x-7)=-2 |